Preparation method of N-type polymer transistor based on titanium / aluminum / titanium laminated contact electrode

By using a titanium/aluminum/titanium stacked contact electrode fabrication method, the problem of precise doping in existing transistors has been solved, enabling the fabrication of high-performance N-type polymer transistors, improving electrical performance and reducing costs.

CN121368327APending Publication Date: 2026-01-20WUXI INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511488090.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-17
Publication Date
2026-01-20

AI Technical Summary

Technical Problem

Existing transistors are difficult to modulate their conductivity type and off-state current through precise local doping using methods such as ion implantation, which limits the application of CMOS-like inverters.

Method used

A method for fabricating N-type polymer transistors using titanium/aluminum/titanium stacked contact electrodes involves vacuum evaporation of multiple metal electrodes, followed by spin-coating and annealing of polymer semiconductor and gate dielectric layers to form high-performance N-type polymer transistors.

Benefits of technology

This improves the electrical performance of N-type polymer transistors, reduces off-state current, lowers the charge injection barrier between the electrodes and the semiconductor, simplifies the fabrication process, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121368327A_ABST
    Figure CN121368327A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electronic information, in particular to a preparation method of an N-type polymer transistor based on a titanium / aluminum / titanium laminated contact electrode. Comprising the following steps: preparing a semiconductor solution and a gate medium solution, wherein the gate medium solution is prepared by dissolving n-butyl acrylate in a solvent; a source electrode and a drain electrode are prepared by laminating titanium, aluminum and titanium metal particles on a substrate in a vacuum evaporation manner. And performing annealing treatment on the spin-coated semiconductor solution to form a polymer semiconductor layer, and performing annealing treatment on the spin-coated gate dielectric solution to form a polymer gate dielectric layer. And then preparing an aluminum gate electrode by thermal evaporation to obtain a target transistor. According to the method, bipolar transport of the donor-acceptor (bipolar) copolymer field effect transistor can be changed into unipolar transport, off-state current is reduced, the performance of the N-type polymer transistor is improved, meanwhile, cost is reduced, and conditions are created for achieving a complementary circuit.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of electronic information, and particularly relates to a preparation method of an N-type polymer transistor based on a titanium / aluminum / titanium laminated contact electrode. BACKGROUND

[0002] In recent years, the surge in demand for flexible wearable devices has driven the rapid development of organic integrated circuits (ICs). Among these studies, inverters, as the core logic unit for building integrated circuits, have attracted a lot of research attention. Studies have found that the preparation of organic inverters mainly falls into two categories: unipolar and complementary (CMOS). Although unipolar structures exhibit high gain, their high power consumption, low noise tolerance, and complex preparation process severely limit their application in the field of organic ICs. In contrast, CMOS inverters exhibit excellent characteristics, and due to the simplification of their preparation process, they are more likely to be applied to commercial products. CMOS inverters use a complementary working mode of one P-type and one N-type device. In most studies, researchers have successfully achieved high-performance P-type and N-type organic field effect transistors (OFETs) by using different semiconductor materials, and can adjust individual devices to match the performance of both. However, this method increases the complexity of the preparation process, which is not conducive to large-scale preparation. Therefore, the application of bipolar organic semiconductors (OSCs) in CMOS-like inverters has attracted widespread interest. However, unlike silicon-based devices, organic transistors are difficult to locally dope to modulate their conductivity type through ion implantation and other means. In order to solve this problem, researchers mainly start from the source / drain (S / D) contact to modulate the charge injection type. Therefore, achieving effective charge injection becomes crucial. SUMMARY

[0003] In order to solve the problem that existing transistors are difficult to precisely locally dope to modulate their conductivity type and regulate off-state current through ion implantation and other means, the application provides a preparation method of an N-type polymer transistor based on a titanium / aluminum / titanium laminated contact electrode.

[0004] The specific technical solutions are as follows: Firstly, the application provides a preparation method of an N-type polymer transistor based on a titanium / aluminum / titanium laminated contact electrode, which comprises the following steps: Step S1: preparation of a solution: Step S1-1: preparation of a semiconductor solution: a bipolar polymer semiconductor material is prepared into a solution with an organic solvent at a mass / volume ratio of 3-10 mg / mL, and is heated to be fully dissolved to obtain a semiconductor solution, The bipolar polymer semiconductor material is a polymer DPPT-TT of 1,4-dioxo-di-pyrrole and thiophene (CAS No. 1260685-66-2), and the organic solvent is o-dichlorobenzene (DCB); 1,4-dioxo-di-pyrrole and thiophene polymer (DPPT-TT), CAS No. 1260685-66-2, molecular formula as follows: .

[0005] Step S1-2: Preparation of gate medium solution: poly (methyl methacrylate) (PMMA) is dissolved in n-butyl acrylate (N-BA), then heated and fully dissolved to form a gate medium solution; PMMA, CAS No. 9011-14-7, molecular formula [CH2C(CH3)(CO2CH3)] n Specifically as follows: .

[0006] Step S2: Cleaning of the substrate; Step S3: Preparation of the device: Step S3-1: Preparation of titanium / aluminum / titanium source-drain electrode: a vacuum evaporation boat, a source-drain mask and a substrate are sequentially placed from top to bottom in a deposition instrument cavity, the vacuum evaporation boat includes evaporation boat one and evaporation boat two placed side by side, titanium metal particles and aluminum metal particles are first placed on evaporation boat one and evaporation boat two respectively, then the source-drain mask cleaned is placed on the substrate, the deposition instrument cavity is pumped to a vacuum -5 ~10 -4 Pa, then vacuum evaporation is performed, evaporation boat one is first heated to prepare a titanium electrode, then evaporation boat two is heated to prepare an aluminum electrode, and then evaporation boat one is heated to prepare a titanium electrode, thereby forming a titanium / aluminum / titanium source-drain electrode on the surface of the substrate; different metals are vacuum evaporated in different time periods by different evaporation boats to form a multi-layer metal electrode. The difference between the present application and the prior art lies in that the electrode is prepared by using multiple metal layers and the method of vacuum evaporation. The electrical performance of the N-type polymer transistor is improved, and the off-state current is inhibited.

[0007] Step S3-2: Preparation of a polymer semiconductor layer: the semiconductor solution is spin-coated on the surface of the sample obtained in step S3-1, and a polymer semiconductor layer is formed on the surface of the titanium / aluminum / titanium source-drain electrode after annealing treatment; Step S3-3: Preparation of a polymer gate medium layer: the gate medium solution is spin-coated on the surface of the sample obtained in step S3-2, and a polymer gate medium layer is formed on the surface of the polymer semiconductor layer after annealing treatment after the end; Step S3-4: Gate electrode preparation: first, place the aluminum metal particles on the vacuum evaporation boat, then place the cleaned gate mask on the surface of the sample obtained in step S3-3, and then evacuate the evaporation instrument cavity to a vacuum of 10 -5 ~10 -4 Pa, and then vacuum evaporation is performed to form an aluminum gate electrode on the surface of the polymer gate dielectric layer. Step S4: Obtain a transistor: adjust the power at both ends of the vacuum evaporation boat, and after cooling to room temperature, fill the inert gas, and after the pressure in the evaporation instrument cavity is balanced with the outside, take out the N-type polymer transistor based on the titanium-aluminum-titanium layered source-drain electrode.

[0008] Further, the specific steps of step S2 are: sequentially placing the substrate in deionized water and alcohol, respectively cleaning the surface impurities by ultrasonic cleaning, then blowing dry with inert gas, and then heating to evaporate the surface.

[0009] Further, in step S3-1, the source-drain mask is made of stainless steel, and the substrate is a glass sheet, wherein the specific steps of vacuum evaporation are: first, heat evaporation boat one, rotate the power control knob to make the vacuum evaporation current reach 170-200 A, prepare a titanium electrode with a thickness of 5-6 nm at a rate of 0.01-0.02 nm / s, then slowly reduce the power, then heat evaporation boat two, rotate the power control knob to make the vacuum evaporation current reach 100-130 A, prepare an aluminum electrode with a thickness of 20-25 nm at a rate of 0.01-0.02 nm / s, then slowly reduce the power, then heat evaporation boat one, rotate the power control knob to make the vacuum evaporation current reach 170-200 A, prepare a titanium electrode with a thickness of 5-6 nm at a rate of 0.01-0.03 nm / s; step S3-1 further comprises the following steps: then slowly reduce the power, fill the inert gas when the evaporation instrument cavity cools to room temperature, and open the evaporation instrument cavity to take out the prepared sample. Compared with the traditional gold electrode as the source-drain electrode of the organic field effect transistor, the metal work function of titanium / aluminum / titanium is lower, and it is more matched with the lowest unoccupied molecular orbital (LUMO) of the bipolar semiconductor material DPPT-TT, and has a smaller electron injection barrier. Therefore, by using the present application, the electrical performance of the N-type organic field effect transistor can be improved. The present application proposes the idea of using titanium / aluminum / titanium as a metal electrode material to form a high-performance N-type contact with an organic semiconductor material, which can not only be used to prepare a high-performance N-type organic transistor, but also can be used to prepare an organic semiconductor material or similar microelectronic device, including a carbon nanotube diode, a light emitting device, a light detector, a biological and chemical sensor device.

[0010] Further, the spin coating process in steps S3-2 and S3-3 is pre-spin coating at 500-600 rpm for 3-5 seconds, and then spin coating at 2000-2100 rpm for 60-120 seconds; the annealing treatment in step S3-2 is 200-250℃ annealing for 1-1.5 hours, and the annealing treatment in step S3-3 is 75-85℃ annealing for 2-3 hours.

[0011] Further, the specific steps for preparing the gate electrode by thermal evaporation in step S3-4 are as follows: heating the vacuum evaporation boat, rotating the power control knob to make the thermal evaporation current reach 100-120 A, and preparing an aluminum gate electrode with a thickness of 80-100 nm at a rate of 0.02-0.03 nm / s.

[0012] Secondly, the application also provides an N-type polymer transistor prepared by any of the above-mentioned methods, which is a top-gate bottom-contact structure and sequentially comprises a gate electrode, a polymer gate insulating layer, a polymer semiconductor layer, a titanium / aluminum / titanium source-drain electrode and a substrate from top to bottom.

[0013] Thirdly, the application also provides an application of the N-type polymer transistor in a flexible electronic, sensor or low-power device.

[0014] Compared with the prior art, the application has the beneficial effects that: using titanium / aluminum / titanium as the metal electrode not only changes the donor-acceptor (bipolar) copolymer (DPPT-TT) field effect transistor from bipolar transport to unipolar transport, reduces the off-state current, reduces the charge injection barrier between the electrode and the semiconductor, improves the performance of the N-type polymer transistor, and reduces the cost, thereby creating conditions for realizing a complementary circuit. BRIEF DESCRIPTION OF DRAWINGS

[0015] Figure 1 Fig. 3 is a 3D structure schematic diagram of the titanium / aluminum / titanium contact field effect transistor of the application; Figure 2 Fig. 4 is a transfer characteristic curve comparison diagram of the N-type field effect transistor prepared by the titanium / aluminum / titanium electrode and the gold electrode of the application; Figure 3 Fig. 5 is an output characteristic curve diagram of the N-type field effect transistor prepared by the titanium / aluminum / titanium electrode and the gold electrode of the application; Figure 4 Fig. 6 is a contact resistance comparison diagram of the N-type field effect transistor prepared by the titanium / aluminum / titanium electrode and the gold electrode of the application. DETAILED DESCRIPTION

[0016] The technical solutions of the application will be described in detail below through examples, but the protection scope of the application is not limited to the examples. Example

[0017] Step S1: Preparation of solution: Step S1-1: Preparation of semiconductor pre-solution; polymer DPPT-TT (CAS No: 1260685-66-2) of 1,4-dioxo-di-pyrrole and thiophene was prepared with o-dichlorobenzene (DCB) at a mass-volume ratio of 5 mg / mL to form a semiconductor solution with a concentration of 5 mg / mL.

[0018] Step S1-2: Preparation of gate medium pre-solution; PMMA and n-butyl acrylate (N-BA) solution were prepared at a mass-volume ratio of 80 mg / mL to form a gate medium pre-solution.

[0019] Step S1-3: Dissolution of solution; the semiconductor pre-solution prepared in step S1-1 was heated on a heating table at 80°C for 48 hours, and the gate medium pre-solution prepared in step S1-2 was heated on a heating table at 80°C for 24 hours, and were fully dissolved respectively to obtain a semiconductor solution and a gate medium solution; Step S2: Cleaning of substrate; the substrate was sequentially placed in deionized water and alcohol and cleaned for 20 minutes by an ultrasonic cleaner respectively, and then dried by a nitrogen gun and heated on a heating table at 100°C for 15 minutes.

[0020] Step S3: Preparation of device: Step S3-1: Preparation of source-drain electrode; titanium metal particles and aluminum metal particles were placed on a vacuum evaporation boat respectively, and then a stainless steel source-drain mask was placed on a glass sheet and sent into the cavity of an evaporation instrument, a mechanical pump and a molecular pump were used to evacuate the cavity of the evaporation instrument to a vacuum of 4×10 -4 Pa, and then a vacuum evaporation method was used, the vacuum evaporation boat was divided into evaporation boat one and evaporation boat two, evaporation boat one was heated, the power control knob was rotated and adjusted so that the vacuum evaporation current reached 200 A, a titanium electrode with a thickness of 5 nm was prepared at a rate of 0.02 nm / s, then the power was slowly reduced, evaporation boat two was heated, the power control knob was rotated and adjusted so that the vacuum evaporation current reached 130 A, an aluminum electrode with a thickness of 20 nm was prepared at a rate of 0.02 nm / s, then the power was slowly reduced, evaporation boat one was heated again, the power control knob was rotated and adjusted so that the vacuum evaporation current reached 200 A, a titanium electrode with a thickness of 5 nm was prepared at a rate of 0.01 nm / s, then the power was slowly reduced, and the cavity was cooled for 30 minutes to form a titanium / aluminum / titanium source-drain electrode on the surface of the glass sheet, and then the cavity was filled with nitrogen to take out the sample. Step S3-2: Preparation of the polymer semiconductor layer: using the semiconductor solution obtained in step S1-3, i.e., the DPPT-TT solution, pre-spin coating at 500 rpm for 5 seconds on the sample surface, then spin coating at 2000 rpm for 60 seconds, and annealing treatment at 200°C for 1 hour to form a polymer semiconductor layer, and after the end of the process, cooling for 40 min.

[0021] Step S3-3: Preparation of the polymer gate medium layer: using the gate medium solution obtained in step S1-3, pre-spin coating at 500 rpm for 3 seconds on the sample obtained in step S3-2, then spin coating at 2000 rpm for 60 seconds, and forming a polymer gate medium layer on the surface of the polymer semiconductor layer by annealing treatment at 80°C for 2 hours.

[0022] Step S3-4: Preparation of the gate electrode: first, place the aluminum metal particles on the vacuum evaporation boat, then place the cleaned gate mask on the sample surface obtained in step S3-3, use a mechanical pump and a molecular pump to pump the evaporation instrument cavity to a vacuum of 4 x 10 -4 Pa, then heat the evaporation boat by hot evaporation, rotate the power control knob to make the hot evaporation current reach 120 A, and form an aluminum gate electrode with a thickness of 80 nm on the surface of the polymer gate medium layer at a rate of 0.02 nm / s.

[0023] Step S4: Preparation of the transistor: adjust the power of the vacuum evaporation boat, and after 30 minutes of cooling, fill nitrogen gas to take out the N-type polymer transistor based on the titanium-aluminum-titanium stack structure as the source-drain electrode. The prepared transistor structure is shown in Figure 1 .

[0024] Polymer field effect transistor using gold as the source-drain electrode.

[0025] Step S1: Preparation of the solution: Step S1-1: Preparation of the semiconductor pre-solution: prepare the polymer DPPT-TT (CAS No.: 1260685-66-2) of 1,4-dioxo-di-pyrrole and thiophene with o-dichlorobenzene (DCB) at a mass-volume ratio of 5 mg / mL to form a semiconductor solution with a concentration of 5 mg / mL.

[0026] Step S1-2: Preparation of the gate medium pre-solution: prepare the PMMA and n-butyl acrylate (N-BA) solution at a mass-volume ratio of 80 mg / mL to form a gate medium pre-solution.

[0027] Step S1-3: dissolution of solution: the semiconductor pre-solution prepared in step S1-1 was heated on a heating table at 80℃ for 48 hours, and the gate medium pre-solution prepared in step S1-2 was heated on a heating table at 80℃ for 24 hours, and then the semiconductor solution and the gate medium solution were fully dissolved, respectively; Step S2: cleaning of substrate; the substrate was sequentially placed in deionized water and alcohol, and cleaned by an ultrasonic cleaner for 20 minutes, respectively, and then dried by a nitrogen gun, and heated on a heating table at 100℃ for 15 minutes.

[0028] Step S3: preparation of device: Step S3-1: preparation of source-drain electrode: gold metal particles and nickel metal particles were placed on a vacuum evaporation boat, respectively, and the vacuum evaporation boat was divided into evaporation boat one and evaporation boat two, then the cleaned stainless steel source-drain mask was placed on the glass sheet and sent into the cavity of the evaporation instrument, and the cavity of the evaporation instrument was pumped to a vacuum of 4×10 -4 Pa, then the evaporation boat two was heated by vacuum evaporation, the power control knob was adjusted by rotation, so that the vacuum evaporation current reached 200A, and the nickel electrode with a thickness of 5nm was prepared at a rate of 0.02nm / s, then the power was slowly reduced, the evaporation boat one was heated, the power control knob was adjusted by rotation, so that the vacuum evaporation current reached 130A, and the gold electrode with a thickness of 20nm was prepared at a rate of 0.02nm / s, then the power was slowly reduced, and the cavity was cooled for 30 minutes, then nitrogen was filled to open the cavity and take out the sample, and the source-drain electrode was prepared; this is different from the embodiment.

[0029] Step S3-2: preparation of polymer semiconductor layer: the surface of the glass sheet was cleaned by air blowing, the semiconductor solution obtained in step S1-3, i.e. the DPPT-TT solution, was used, and the glass sheet was pre-spun at 500rpm for 3-5 seconds by a pipette, then spun at 2000rpm for 60 seconds, and then annealed at 200℃ for 1 hour to form a polymer semiconductor layer on the glass sheet, and then cooled for 40 minutes; Step S3-3: preparation of polymer gate medium layer: the surface of the glass sheet was cleaned by air blowing, and the gate medium solution obtained in step S1-3 was used, and the sample obtained in step S3-2 was pre-spun at 500rpm for 3 seconds by a pipette, then spun at 2000rpm for 60 seconds, and then annealed at 80℃ for 2 hours to form a polymer gate medium layer on the surface of the polymer semiconductor layer.

[0030] Step S3-4: preparation of gate electrode: aluminum metal particles were placed on a vacuum evaporation boat, then the cleaned gate mask was placed above the surface of the sample obtained in step S3-3, and the cavity of the evaporation instrument was pumped to a vacuum of 4×10 -4Pa, then the way of thermal evaporation is used to heat the evaporation boat, the rotating adjustment power control knob, so that the thermal evaporation current reaches 120 A, at a rate of 0.02 nm / s on the surface of the polymer gate dielectric layer to form a thickness of 80 nm aluminum gate electrode.

[0031] Step S4: the transistor is prepared: adjust the power at both ends of the vacuum evaporation boat, and after cooling, fill nitrogen to take out the N-type polymer transistor based on gold as the source and drain electrode.

[0032] Figure 1 The 3D structure schematic diagram of the N-type organic field effect transistor prepared in the embodiment; Figure 2 The N-type saturation region transfer characteristic curve comparison diagram of the organic field effect transistor obtained in the comparative example and the embodiment. See Figure 2 It can be seen that the performance of the transfer characteristic curve of the organic field effect transistor prepared in the embodiment based on titanium / aluminum / titanium as the source and drain electrode is better than that of the conventional transistor based on gold as the source and drain electrode, and all the basic electrical parameters are superior to the latter. As shown in Table 1, the threshold voltage, mobility, sub-threshold swing and current on-off ratio of the two devices are listed. For the organic field effect transistor of the comparative example, the threshold voltage is 33.8 V, the mobility is 0.03 cm 2 / V·s, the sub-threshold swing is 9.4 V / dec, and the current on-off ratio is 1005. For the organic field effect transistor of the embodiment, the threshold voltage is 16.4 V, the mobility is 0.126 cm 2 / V·s, the sub-threshold swing is 3.6 V / dec, and the current on-off ratio is 18717. From the above electrical parameter indicators, it can be seen that the electrical performance of the polymer field effect transistor prepared by the present application has been significantly improved.

[0033] Table 1 Device conditions Threshold voltage (V) Mobility (cm 2 / V·s)]]> Subthreshold swing (V / dec) Current switching ratio Ti / Al / Ti 16.4 0.126 3.6 18717 Au 33.8 0.030 9.4 1005 Figure 3 The N-type output characteristic curve comparison diagram of the organic field effect transistor obtained in the comparative example and the embodiment. As Figure 3 It can be seen that the saturation current of the output characteristic curve of the organic field effect transistor prepared in the embodiment based on titanium / aluminum / titanium as the source and drain electrode is superior to that of the conventional transistor based on gold as the source and drain electrode. At the same time, we can also find from the vicinity of the origin of the output curve that the OFET of titanium / aluminum / titanium electrode has better linearity, which indicates better N-type contact.

[0034] Figure 4 The contact resistance of the organic field effect transistor obtained in the comparative example and the embodiment R c) Comparison plots. The data of contact resistance obtained from transmission line method (TLM) show the trend of channel width normalized R c variation at different gate voltages (from 5 to 35 V). The data show that the R c of Al / Ti devices is much lower than that of Au devices, Al / Ti is about 0.85 to 4 x 10 6 Ω·cm, while the R c of Au devices is between 2 to 50 x 10 6 Ω·cm.

[0035] The results show that the performance of the device with titanium / aluminum / titanium as source-drain electrode is significantly improved compared with the device with gold as source-drain electrode. At the same time, the preparation cost is greatly reduced, which provides a direction for future large-scale application.

[0036] The above-mentioned technologies not specifically mentioned are referred to the prior art.

[0037] As described above, although the present application has been shown and described with respect to particular preferred embodiments, it is to be understood that the application is not limited to the details of the foregoing illustrative examples, but rather can be used with any other variations omissions, and embodiments that are apparent from this disclosure. The intended scope of the application is, therefore, indicated by the following claims.

Claims

1. A method for fabricating an N-type polymer transistor based on a titanium / aluminum / titanium stacked contact electrode, characterized by, The method comprises the following steps: Step S1: preparation of a solution Step S1-1: preparation of a semiconductor solution: a bipolar polymer semiconductor material is prepared into a solution with an organic solvent at a mass-volume ratio of 3-10 mg / mL, and heated to fully dissolve, to obtain a semiconductor solution, The bipolar polymer semiconductor material is a polymer DPPT-TT (CAS No. 1260685-66-2) of 1,4-dioxo di-pyrrole and thiophene, and the organic solvent is o-dichlorobenzene (DCB); Step S1-2: preparation of a gate medium solution: polymethyl methacrylate (PMMA) is dissolved in n-butyl acrylate (N-BA), and then heated and fully dissolved to form a gate medium solution; Step S2: cleaning of a substrate Step S3: preparation of a device Step S3-1: Preparation of the titanium / aluminum / titanium source drain electrode: Place the vacuum evaporation boat, the source drain mask and the substrate in the evaporation instrument cavity from top to bottom in sequence, the vacuum evaporation boat includes evaporation boat one and evaporation boat two placed side by side, first place the titanium metal particles and the aluminum metal particles on evaporation boat one and evaporation boat two respectively, then cover the cleaned source drain mask on the substrate, evacuate the evaporation instrument cavity to a vacuum of 10 -5 ~10 -4 Pa, then perform vacuum evaporation, first heat evaporation boat one to prepare the titanium electrode, then heat evaporation boat two to prepare the aluminum electrode, and then heat evaporation boat one to prepare the titanium electrode, thereby forming the titanium / aluminum / titanium source drain electrode on the surface of the substrate; Step S3-2: preparation of a polymer semiconductor layer: the semiconductor solution obtained in step S3-1 is spin-coated on the surface of the sample, and after the end of the process, annealing treatment is performed to form a polymer semiconductor layer on the surface of the titanium / aluminum / titanium source-drain electrode; Step S3-3: preparation of a polymer gate medium layer: the gate medium solution obtained in step S3-2 is spin-coated on the surface of the sample, and after the end of the process, annealing treatment is performed to form a polymer gate medium layer on the surface of the polymer semiconductor layer; Step S3-4: Gate electrode preparation: First, place the aluminum metal particles on the second vacuum evaporation boat, then place the cleaned gate mask on the surface of the sample obtained in step S3-3 above, and evacuate the evaporation instrument cavity to a vacuum of 10 -5 ~10 -4 Pa, and then vacuum evaporate to form an aluminum gate electrode on the surface of the polymer gate dielectric layer; Step S4: preparation of a transistor: the power at both ends of the vacuum evaporation boat is adjusted to reduce, and after cooling to room temperature, inert gas is filled, and after the gas pressure in the evaporation instrument cavity is reduced to balance with the outside, the N-type polymer transistor based on the titanium-aluminum-titanium layered source-drain electrode is taken out.

2. The production method according to claim 1, characterized by, The specific steps of step S1-2 are: PMMA and n-butyl acrylate (N-BA) solution are prepared into a PMMA N-BA solution at a mass-volume ratio of 80 mg / mL.

3. The preparation method according to claim 1, characterized in that, In steps S1-1 and S1-2, heating is performed to 75-85°C to fully dissolve.

4. The preparation method according to claim 1, characterized in that, The specific steps of step S2 are: the substrate is sequentially placed in deionized water and alcohol, and the surface impurities are removed by ultrasonic cleaning, and then the inert gas is blown dry, and the surface is evaporated dry by heating.

5. The preparation method according to claim 1, characterized in that, In step S3-1, the source-drain mask material is stainless steel, and the substrate is a glass sheet, wherein the specific steps of vacuum evaporation are: first, evaporating boat one is heated, the power control knob is rotated to adjust, so that the vacuum evaporation current reaches 170-200 A, a titanium electrode with a thickness of 5-6 nm is prepared at a rate of 0.01-0.02 nm / s, then the power is slowly reduced, evaporating boat two is heated, the power control knob is rotated to adjust, so that the vacuum evaporation current reaches 100-130 A, an aluminum electrode with a thickness of 20-25 nm is prepared at a rate of 0.01-0.02 nm / s, then the power is slowly reduced, and then evaporating boat one is heated, the power control knob is rotated to adjust, so that the vacuum evaporation current reaches 170-200 A, a titanium electrode with a thickness of 5-6 nm is prepared at a rate of 0.01-0.03 nm / s; step S3-1 further comprises the following steps: then the power is slowly reduced, the inert gas is filled after the evaporation instrument cavity is cooled to room temperature, and the prepared sample is taken out by opening the evaporation instrument cavity.

6. The method of claim 1, wherein, The spin coating process in steps S3-2 and S3-3 is pre-spinning at 500-600 rpm for 3-5 seconds, and then spinning at 2000-2100 rpm for 60-120 seconds; the annealing treatment in step S3-2 is annealing at 200-250 ℃ for 1-1.5 hours, and the annealing treatment in step S3-3 is annealing at 75-85 ℃ for 2-3 hours.

7. The preparation method according to claim 1, characterized in that, The specific steps for preparing the gate electrode by the thermal evaporation method in step S3-4 are as follows: heating the vacuum evaporation boat, rotating the power control knob to make the thermal evaporation current reach 100-120 A, and preparing an aluminum gate electrode with a thickness of 80-100 nm at a rate of 0.02-0.03 nm / s.

8. An N-type polymer transistor prepared by the method of any one of claims 1-7, wherein the transistor is a top-gate bottom-contact structure, and sequentially comprises, from top to bottom, a gate electrode, a polymer gate insulating layer, a polymer semiconductor layer, a titanium / aluminum / titanium source-drain electrode, and a substrate.

9. Use of the N-type polymer transistor of claim 8 in a flexible electronic, sensor, or low-power device.